2022
DOI: 10.1093/aobpla/plac011
|View full text |Cite
|
Sign up to set email alerts
|

The relative role of plasticity and demographic history in Capsella bursa-pastoris: a common garden experiment in Asia and Europe

Abstract: Background and aims The colonization success of a species depends on the interplay between its phenotypic plasticity, adaptive potential and demographic history. Assessing their relative contributions during the different phases of a species range expansion is challenging, and requires large-scale experiments. Here, we investigated the relative contributions of plasticity, performance and demographic history to the worldwide expansion of the shepherd’s purse, Capsella bursa-pastoris. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…In contrast, within C. bursa-pastoris , the ranking among genetic clusters does not differ across experiments, where ASI populations, corresponding to the expansion front of the species ( Cornille et al , 2016 ), performed the worst and were the least competitive. This is in line with their higher genetic load ( Kryvokhyzha et al , 2019 ) and with the limited evidence of local adaptation at large geographical scale where ASI populations performed the worst under three different environments, including their native environment, in China ( Cornille et al , in press ).…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, within C. bursa-pastoris , the ranking among genetic clusters does not differ across experiments, where ASI populations, corresponding to the expansion front of the species ( Cornille et al , 2016 ), performed the worst and were the least competitive. This is in line with their higher genetic load ( Kryvokhyzha et al , 2019 ) and with the limited evidence of local adaptation at large geographical scale where ASI populations performed the worst under three different environments, including their native environment, in China ( Cornille et al , in press ).…”
Section: Discussionmentioning
confidence: 55%
“…Distinguishing between the relative importance of plasticity and adaptation for this success will require further study. Common garden experiments in C. bursa‐pastoris from the Eurasian range have shown that phenology is plastic for the species but it also has genetic variation across the range (Cornille et al, 2022). Experiments have shown that phenology shifts affect competition, potentially allowing C. bursa‐pastoris to persist in highly competitive environments (Orsucci et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As it colonized North America, it invaded both higher and lower latitudes than in its native range of Europe. C. bursa‐pastoris exhibits latitudinal and elevational clines in flowering time, and some populations are more responsive than others to environmental cues for flowering (Neuffer and Hoffrogge, 1999; Cornille et al, 2022). Additionally, Orsucci et al (2020) showed that C. bursa‐pastoris plants that flowered earlier than their counterparts were less affected by competition, potentially because the plants avoided interspecific competition.…”
mentioning
confidence: 99%
“…Our work showing shifts in the seasonal niche fit in with other work on phenology in C. bursa-pastoris. For example, common garden experiments in C. bursa-pastoris have shown 13 that phenology is plastic but also has genetic variation across the range (Cornille et al, 2022) and that phenology shifts affect competition, potentially allowing C. bursa-pastoris to persist in highly-competitive environments (Orsucci et al, 2020). Understanding the mechanism through which C. bursa-pastoris has managed to quickly expand its range could reveal broader patterns of evolution in invasive species, especially other polyploids and selfers.…”
Section: Discussionmentioning
confidence: 99%
“…As it colonized North America, it invaded both higher and lower latitudes than in its native range of Europe. C. bursa-pastoris exhibits latitudinal and elevational clines in flowering time, and some populations are more responsive than others to environmental cues for flowering (Neuffer and Hoffrogge, 1999; Cornille et al, 2022). Additionally, (Orsucci et al, 2020) showed that C. bursa-pastoris plants that flowered earlier than their counterparts were less affected by competition, potentially because the plants avoided interspecific competition.…”
Section: Introductionmentioning
confidence: 99%